Research progress on the induction of melanocytes in vitro. - Wang, S.; Zhang, R. (European Journal of Pediatric Dermatology, 2022)
The transplantation of melanocytes (MCs) is an effective treatment for intractable stationary vitiligo. Since MCs are difficult to culture and expand in vitro, it is necessary to develop improved methods to obtain, culture and expand them. So far, various types of stem cells have been induced to differentiate into MCs, including embryonic stem cells, dental pulp stem cells, mesenchymal stem cells and induced pluripotent stem cells. Meanwhile, some types of somatic cells have also been transdifferentiated into MCs. The successful induction of MCs in vitro not only will produce sufficient numbers of MCs for clinical use, but also will facilitate research on the development and differentiation of MCs. This review describes in detail various protocols used to induce the differentiation of stem cells and to transform terminally-differentiated somatic cells into MCs, and compares the advantages and disadvantages of those protocols. This review provides comprehensive background data for selecting the most optimal conditions to obtain and culture MCs.